ANALYSIS OF THE FREE LEARNING - INDEPENDENT CAMPUS (MBKM) POLICY - Hijrawati Rusman; Muhammad Takdir; Mursak Mursak; Salman Salman (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2024)
This study investigates the impact of the Student Exchange Program on students of the Government Science Study Program at Muhammadiyah University of Sinjai in the context of implementing the Independent Campus Learning Policy (MBKM). Research methods involve observations of students' direct participation in the program, as well as interviews to gain an in-depth understanding of their experiences. Observation results show that this program has had a significant impact on the development of academic Government Studies, analysis of political and government issues, as well as students' ability to formulate solutions and analyze community resources. Interviews revealed that students also experienced improved social skills, such as adaptability, cross-cultural communication, and leadership, as well as gaining broader career opportunities and international collaboration in the future. In conclusion, this student exchange program not only provides great academic benefits, but also helps students in holistic self-development, thereby making a significant contribution in forming a generation of students who are ready to compete globally.